The Effect of Fascia Iliaca Compartment Blockade on Mortality in Patients With Hip Fractures: Systematic Review and Meta-analysis of Randomized Controlled Trials. Issue 3 (1st February 2022) - Baker, Hayden P.; Portney, Daniel A.; Schroedl, Liesl M.; Strelzow, Jason A.; Hynes, Kelly; Dillman, Daryl B.
Abstract : Objective: The purpose of this meta-analysis was to determine whether perioperative fascia iliaca compartment blockade (FICB) decreases mortality in patients with hip fracture. Methods: MEDLINE (PubMed and Ovid platforms), Web of Science, EMBASE, and Cochrane Database of Systemic Reviews were screened for "fascia iliaca compartment block, hip fracture" articles in English, in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, from January 1, 2005, to March 1, 2020. All relevant randomized controlled trials and cohort and case-control studies were included for analysis. Relevant article titles were identified, and their corresponding abstracts were independently reviewed by two authors for inclusion. The full-text articles were then obtained for all relevant identified abstracts and assessed for inclusion in the meta-analysis. Conflicts in quality assessment between the two independent reviewers were resolved by a consensus vote of all authors. Results: Study quality was assessed objectively using the Jadad and Newcastle-Ottawa Scale. This meta-analysis was done in accordance with the PRISMA (http://links.lww.com/JAAOS/A731 ) and QUORUM guidelines. Quantitative synthesis analysis was done using Cochrane Reviews Review Manager (version 5.3). All analyses were completed using random-effects models and comparing the individual effect sizes within each study. Discussion: Management of hip fracture pain with FICB does not markedly decrease short-term mortality. Our findings support the continued use of FICB for the management of hip fractures in geriatric patients and suggest the need for future prospective randomized controlled trials to further determine FICB's effect on short-term and long-term mortality and functional status. Level of Evidence: Therapeutic level I